2006
DOI: 10.1515/bc.2006.078
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-converting enzyme inhibitor peptides derived from the endostatin-containing NC1 fragment of human collagen XVIII

Abstract: Extracellular matrix and soluble plasma proteins generate peptides that regulate biological activities such as cell growth, differentiation and migration. Bradykinin, a peptide released from kininogen by kallikreins, stimulates vasodilatation and endothelial cell proliferation. Various classes of substances can potentiate these biological actions of bradykinin. Among them, the best studied are bradykinin potentiating peptides (BPPs) derived from snake venom, which can also strongly inhibit angiotensin I-conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Cathepsins L and S cleaved Endo-08 and Endo-09 between residues His-1344 and Leu-1345, and Endo-10 between Ala-1347 and Leu-1348 (human collagen XVIII numbering). These findings are in agreement with the previously proposed cleavage sites of the NC-1 domain, but they do not match any of N-terminal forms of circulating endostatin that have been characterized (9,19,20). However, cathepsin B cleaved Endo-09 between Leu-1345 and Val-1346, which does correspond to the N terminus of the shorter molecular variety of endostatin (ϳ20 kDa) found in human plasma for which no other candidate protease has been identified to date (9).…”
Section: In Vitro Release Of Human Endostatin By Cysteine Cathepsins-supporting
confidence: 86%
“…Cathepsins L and S cleaved Endo-08 and Endo-09 between residues His-1344 and Leu-1345, and Endo-10 between Ala-1347 and Leu-1348 (human collagen XVIII numbering). These findings are in agreement with the previously proposed cleavage sites of the NC-1 domain, but they do not match any of N-terminal forms of circulating endostatin that have been characterized (9,19,20). However, cathepsin B cleaved Endo-09 between Leu-1345 and Val-1346, which does correspond to the N terminus of the shorter molecular variety of endostatin (ϳ20 kDa) found in human plasma for which no other candidate protease has been identified to date (9).…”
Section: In Vitro Release Of Human Endostatin By Cysteine Cathepsins-supporting
confidence: 86%
“…34 Interestingly, a recent study showed that the internal peptide sequence of endostatin resembles an ACE-inhibitory peptide, called bradykininpotentiating peptide, and that the synthetic peptide of the sequence indeed inhibited ACE catalytic activity. 23,24,35 Thus, endostatin or its degraded peptide fragments are implicated as a putative ACEI. Taking all the evidence together, endostatin is a negative regulator of protease-mediated adverse tissue remodeling in the infarcted heart.…”
Section: Discussionmentioning
confidence: 99%
“…158) Various ACE inhibitory peptides derived from animals and plants have been found. 159) An amino acid sequence of the NC1 domain of type XVIII collagen in the vicinity of endostatin resembles the snake venom-derived bradykinin-potentiating peptides, which strongly inhibit ACE activity. 160) Isobe et al reported that an anti-endostatin antibody increased ACE activity in the infarcted myocardium.…”
Section: Possibile Application Of Basement Mem-brane-derived Matricrymentioning
confidence: 99%